New method of neck surface electromyography for the evaluation of tongue‐lifting activity. (10th February 2016) - Manda, Y.; Maeda, N.; Pan, Q.; Sugimoto, K.; Hashimoto, Y.; Tanaka, Y.; Kodama, N.; Minagi, S.
Summary: Elevation of the posterior part of the tongue is important for normal deglutition and speech. The purpose of this study was to develop a new surface electromyography (EMG) method to non‐invasively and objectively evaluate activity in the muscles that control lifting movement in the posterior tongue. Neck surface EMG (N‐EMG) was recorded using differential surface electrodes placed on the neck, 1 cm posterior to the posterior border of the mylohyoid muscle on a line orthogonal to the lower border of the mandible. Experiment 1: Three healthy volunteers (three men, mean age 37·7 years) participated in an evaluation of detection method of the posterior tongue lifting up movement. EMG recordings from the masseter, temporalis and submental muscles and N‐EMG revealed that i) N‐EMG was not affected by masseter muscle EMG and ii) N‐EMG activity was not observed during simple jaw opening and tongue protrusion, revealing the functional difference between submental surface EMG and N‐EMG. Experiment 2: Seven healthy volunteers (six men and one woman, mean age 27·9 years) participated in a quantitative evaluation of muscle activity. Tongue‐lifting tasks were perfor‐med, exerting a prescribed force of 20, 50, 100 and 150 gf with visual feedback. For all subjects, a significant linear relationship was observed bet‐ween the tongue‐lifting force and N‐EMG activity ( P < 0·01). These findings indicate that N‐EMG can be used to quantify the force of posterior tongue lifting and could be useful to evaluate the effect of tongue rehabilitation in future studies.